Self-Perception of Health and Physical Activity Levels Among the Youth and Adults Before and Amidst the COVID-19 Pandemic - Nyawornota, Vida Korleki; Adamba, Clement; Tay, Doris Akosua; Nyanyofio, Oscar C.; Muomah, Rosemary C.; Chukwuorji, JohnBosco C.; Nwonyi, Sampson K.; Malete, Leapetswe; Joachim, Dale; Ocansey, Reginald T. (My University, 2024)
Background: Emerging research indicates that the COVID-19 pandemic and associated restrictions led to decreased physical activity levels and poorer health globally. However, most studies on this topic have focused on advanced countries, leaving a gap in understanding the impact in countries like Ghana. This study aimed to fill this gap by assessing self-perceived health status and physical activity levels among youth and adults in Ghana before, during, and after the COVID-19 restrictions. Understanding these dynamics is crucial for informing public health interventions and policies to promote well-being during and beyond the pandemic. Methods: A cross-sectional survey using online data collection methods was conducted, involving 937 participants. Data included demographic information, and International Physical Activity Questionnaire-Short Form (IPAQ-SF). Analysis was done using SPSS version 25, with descriptive statistics and multinomial regression. Results: Most participants (89.6%) reported good health. Male participants were significantly more likely to engage in moderate (1.78 times) and high (3.17 times) physical activity during the COVID-19 period compared to females. Conclusion: This study highlights gender disparities in physical activity levels during the pandemic in Ghana. Addressing these disparities and promoting healthier lifestyles, especially during crises, is crucial for general and mental health. Further research should explore socio-demographic factors’ role in health behaviors during pandemics.
Keywords: COVID-19; Ghana; physical activity; health status; gender; public health